2021
DOI: 10.2147/ott.s300320
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Lymphoma as a Secondary Neoplasm During Therapy for Chronic Myeloid Leukaemia: Case Report and Review of the Literature

Abstract: Introduction Incidences of chronic myeloid leukaemia (CML) after treatment of Hodgkin lymphoma (HL) are well described. Here, we report a case of secondary HL in a patient with CML treated with dasatinib as a third-line treatment. Patient Information A 64-year-old male was diagnosed with CML and initially treated with imatinib and then with nilotinib due to resistance. Finally, the patient experienced cardiovascular complications, and dasatinib was introduced. After 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Table I summarizes the detailed clinical course of lymphomas reported in the literature to date that occurred during or after TKI treatment in patients with CML 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ; All cases are B-cell lineage lymphoma, and imatinib was the most commonly administered drug. Miranda et al also found an increased standardized incidence ratio of non-Hodgkin lymphomas after imatinib treatment in a long-term observational study of patients with CML.…”
Section: Discussionmentioning
confidence: 99%
“…Table I summarizes the detailed clinical course of lymphomas reported in the literature to date that occurred during or after TKI treatment in patients with CML 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ; All cases are B-cell lineage lymphoma, and imatinib was the most commonly administered drug. Miranda et al also found an increased standardized incidence ratio of non-Hodgkin lymphomas after imatinib treatment in a long-term observational study of patients with CML.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the secondary neoplasia of a T-cell non-Hodgkin’s lymphoma (T-NHL) obscured the diagnosis, leading to the assumption of initial treatment failure. Although concurrent neoplasias are described in CML patients ( 22 25 ), they are still a diagnostic as well as therapeutic challenge. In our case, the atypical phenotype led to the assumption of CML infiltration of the skin, whereas autopsy revealed the diagnosis of a CD2-negative T-NHL.…”
Section: Discussionmentioning
confidence: 99%